2022
DOI: 10.1038/s41598-022-21273-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous amino acids application on the biochemical, antioxidant, and nutritional value of some leafy cabbage cultivars

Abstract: Using organic fertilizer as part of plant nutrition for decreasing using chemical fertilizer and increasing plants’ nutritional value is scientists’ concern. Treatments were three concentrations of a mixture of 16 different AAs (amino acid) (0, 150 and 300 mg/L), sprayed every 7 days for 2 months on 4 leafy cabbages. Results showed 300 mg/L AAs increased anthocyanin, flavonoids, phenol, protein and proline. The SOD, POX and APX rose upon AAs usage. The application of AA significantly increased the total chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…It has been confirmed that antioxidant enzymes play principal role in reducing free radicals; as a result, their stimulation can increase the plant's tolerance to a biotic stresses (Caverzan et al, 2016). Our findings supported the results of other studies (Haghighi et al, 2022, Ardebili et al, 2012. The hypothesis is that amino acids can enhance antioxidant enzyme capacity.…”
Section: Abscisic Acid and Superoxide Dismutasesupporting
confidence: 92%
See 1 more Smart Citation
“…It has been confirmed that antioxidant enzymes play principal role in reducing free radicals; as a result, their stimulation can increase the plant's tolerance to a biotic stresses (Caverzan et al, 2016). Our findings supported the results of other studies (Haghighi et al, 2022, Ardebili et al, 2012. The hypothesis is that amino acids can enhance antioxidant enzyme capacity.…”
Section: Abscisic Acid and Superoxide Dismutasesupporting
confidence: 92%
“…Previous researches have shown that foliar implementation of amino acids biostimulants on cabbage and Aloe vera leaves considerably upsurges antioxidant activities such as CAT, POD, SOD, and APX (El-Beltagi et al, 2010;Ardebili et al, 2012;Haghighi et al, 2020). Similarly, the activity levels of SOD, CAT, POD, and APX were increased by increasing the application of amino acids under normal and stressful conditions, particularly in cabbage plants (Haghighi et al, 2022). It has been confirmed that antioxidant enzymes play principal role in reducing free radicals; as a result, their stimulation can increase the plant's tolerance to a biotic stresses (Caverzan et al, 2016).…”
Section: Abscisic Acid and Superoxide Dismutasementioning
confidence: 95%
“…In this study, metabolomics analysis showed that the contents of 11 amino acids (phenylalanine, tyrosine, alanine, glutamic acid, 5-oxoproline, glutamine, L-ornithine, proline, 4aminobutyric acid, aspartic acid, and asparagine) synthesized from four different precursors (phosphoenolpyruvate, pyruvate, 2oxoglutarate and oxaloacetate) significantly increased after leucine application (Figure 4). As previously reported, the exogenous application of some amino acids can enhance the antioxidant capacity of plants in different ways (Haghighi et al, 2022). For example, aromatic amino acids (phenylalanine, tyrosine, etc.)…”
Section: Exogenous Leucine Enhances the Antioxidant Capacitymentioning
confidence: 89%
“…The availability of nitrogen directly impacts the size and firmness of cabbage heads, with insufficient levels leading to smaller heads with loose leaves and excessive levels causing overly large but less compact heads [ 32 ]. Adequate nitrogen boosts cabbage's nutritional quality by spurring the synthesis of proteins, vitamins, and essential nutrients, enriching its overall value [ 94 ]. Optimal nitrogen levels bolster cabbage plants against pests and diseases by fostering robust growth and enhancing their ability to fend off attacks [ 95 ].…”
Section: Effect Of Nitrogen Levels On Cabbage Qualitymentioning
confidence: 99%